Development Status, Challenges, and Countermeasures in the 'Smooth Trade' Mode of China's Belt and Road Initiative - Du, Jia (Transactions on Economics, Business and Management Research, 2024)
The "the Belt and Road" is a bridge and link connecting economic and trade exchanges between Asia, Africa and Europe. It concerns billions of people around the world. It is also one of the largest comprehensive development planning projects in the big world. In 2013, the General Secretary put forth the vision of collaboratively building the “Belt and Road” Initiative. Over the ensuing 11 years, this concept has transitioned from being a mere idea to being actively implemented, evolving from broad strokes into intricate details. It grounded in the principles of joint consultation, contribution, and shared benefits, has forged friendly cooperation with numerous nations. This paper delves into the current developmental progress of the “unimpeded trade,” “financial connectivity,” aspects within this Initiative. By examining their practical applications in exemplary collaboration cases, we seek to identify underlying challenges and offer well-considered strategies, thereby laying a theoretical foundation for future cooperative endeavors.